INCREASE OF STRAWBERRY (Fragaria sp.) PRODUCTION THROUGH STOLON Pruning STRAWBERRY PLANT YIELD INCREASE THROUGH STOLON PRUNING (Fragaria sp.): PENINGKATAN PRODUKSI TANAMAN STROBERI (Fragaria sp.) MELALUI PEMANGKASAN STOLON STRAWBERRY PLANT YIELD INCREASE THROUGH STOLON PRUNING (Fragaria sp.) - Tafonao, Duhusokhi (LPPM UPMI, 2023)
Increasing the production of strawberry cultivation can be done by pruning the stolons or tendrils that emerge from the mother plant. Stolons, also known as tendrils, are extensions of strawberry shoots that grow horizontally and spread parallel to the soil surface (creeping), and can be used as new plant material for vegetative propagation. The formation of roots, stems, and leaves, the process of forming flowers will be hampered if the stolons are not pruned, this occurs due to competition for the assimilation of results needed by strawberry plants in the process of growth and production. to obtain information from previous research that is relevant to pruning stolons and time so that it has an impact on the production of strawberry plants by planting using polybags. The results showed that the optimal pruning time was carried out at the age of 5 weeks after planting, the use of liquid organic fertilizer increased the diameter and weight of the strawberries, stolons could be used for vegetative propagation, and increased efficient production using media and organic fertilizers to protect the environment and plant yields. Strawberries are safer to eat because they don't use chemical fertilizers.